2001
DOI: 10.1200/jco.2001.19.8.2222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pharmacologic Study of the Epirubicin and Paclitaxel Combination in Women With Metastatic Breast Cancer

Abstract: ET is feasible, devoid of excessive cardiac toxicity, and active. A reciprocal pharmacokinetic interference between the two drugs has pharmacodynamic consequences, and suggests a direct effect of PTX on EPI metabolism requiring ad hoc investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…This figure is significantly higher than that determined for EPI single agent or in combination with agents other than taxanes (15% cumulative risk of CHF at 1000 mg/m 2 EPI) (Ryberg et al, 1998), and it raises the possibility that PTX might increase the cardiotoxicity of EPI the same way it increases that of DOX. Interestingly, pharmacokinetic studies of patients receiving bolus EPI followed immediately by PTX infusion showed that PTX increased plasma exposure to EPIol and to the more polar EPIol or EPI glucuronides without affecting EPI elimination, a result pointing to metabolic rather than pharmacokinetic interference of PTX with EPI (Grasselli et al, 2001).…”
Section: Enhancement By Other Agentsmentioning
confidence: 99%
“…This figure is significantly higher than that determined for EPI single agent or in combination with agents other than taxanes (15% cumulative risk of CHF at 1000 mg/m 2 EPI) (Ryberg et al, 1998), and it raises the possibility that PTX might increase the cardiotoxicity of EPI the same way it increases that of DOX. Interestingly, pharmacokinetic studies of patients receiving bolus EPI followed immediately by PTX infusion showed that PTX increased plasma exposure to EPIol and to the more polar EPIol or EPI glucuronides without affecting EPI elimination, a result pointing to metabolic rather than pharmacokinetic interference of PTX with EPI (Grasselli et al, 2001).…”
Section: Enhancement By Other Agentsmentioning
confidence: 99%
“…Retention times were 11.7 min (doxorubicinol), 12.4 min (doxorubicin), 14.1 min (AL1576), 18.9 min (docetaxel), and 20.6 min (paclitaxel). Anthracyclines were detected fluorimetrically (excitation at 480 nm, emission at 560 nm) (Salvatorelli et al, 2006); paclitaxel and docetaxel were detected by UV absorbance ( max ϭ 230 nm) (Grasselli et al, 2001); and AL1576 was detected by UV absorbance ( max ϭ 270 nm) and fluorescence (excitation at 280 nm, emission at 333 nm) (Barski et al, 1995). All the analytes were quantified against standard curves obtained after comparable extractive and chromatographic procedures.…”
Section: Methodsmentioning
confidence: 99%
“…These concentrations were severalfold lower than in previous studies of rabbit isolated heart (10, 11) but ranged over levels measured in the plasma of patients shortly after standard boluses of DOX (27) or EPI (28). Moreover, all experiments were reconstituted in fresh plasma from healthy donors to account for the known ability of albumin and ␣-acid glycoprotein to bind anthracyclines and limit their partitioning in tissues (29).…”
Section: Characterization Of a Translational Model Of Humanmentioning
confidence: 76%